A holistic model of the inter-firm technology transfer based on integrated perspectives of knowledge-based view and organizational learning - Sazali Abdul Wahab; Raduan Che Rose; Haslinda Abdullah (2009)
The objective of this study is to propose a holistic model of inter-firm technology transfer (TT) based on an integrated knowledge-based-view (KBV) and organizational learning (OL) perspectives in conceptualizing the critical links between technology transfer characteristics: knowledge, technology recipient, technology supplier and relationship characteristics (TTCHARS) and degree of technology transfer (TTDEG) in international joint ventures (IJVs). Since the current TT issue now is centered on efficiency and effectiveness of technology transfer as an efficient formal vehicle to internalize foreign technologies as compared to direct import of goods, licensing and foreign direct investment, the advancement of the holistic model is to provide a complete view on the significant effect of technology transfer characteristics and their dimensions on degree of technology transfer in IJV which eventually could contribute to the increase of local companies’ competitiveness, indigenous technical capabilities, technological development, and potential for local innovation. In the study’s model, hypotheses are developed to describe the relationships between TTCHARS and TTDEG based on the underlying KBV and OL perspectives.